Formación inicial de profesores de ciencias desde los enfoques CTSA y las concepciones Andinas de Vivir bien y Buen vivir (2017)
This article presents a research in the field of the training of science teachers carried out in an unconventional scenario of teaching learning, elective course type, in the Faculty of Science and Technology of the National Pedagogical University called "The relations science, technology, Society and the environment (CTSA) in the training of science professors". In the development of this proposal for curricular training and integration, pedagogical innovation activities and social appropriation of knowledge and knowledge were carried out around emerging issues in teaching such as socio-scientific issues, CTSA relations and paradigms Andinos of Good Living and Living Well, in the key of the initial formation of graduates in natural sciences such as Physics, Chemistry and Biology, and of interdisciplines such as Electronics and Technological Design.